Global Financialization Effects and the Role of Islamic Finance Institutions - ABBAS, MUHAMMAD HASSAN; FAHAD, SHAH (International Journal of Islamic Economics and Governance, 2022)
Financialization refers to the growing importance of financial activities as a source of profits in the economy, distinguishing the dominance of the finance sector over all other industries. This includes the gradual change in operations of many traditional manufacturers who have turned to generate income through financial means rather than the mere provision of goods to their customers. Financialization has increased the power of the rentier class within society, the preeminence of maximizing the shareholder value principle among corporate management, the dominance of capital markets over bank-based finance, and the surge of financial trading with the help of new financial instruments and technology. Several studies argue that there is a massive impact on the economic and financial industry since financialization has become prominent around the globe. Therefore, there is a need to come up with structural changes to support and help the financial industry for its betterment. In this paper, we will discuss the effects of financialization in several studies and explore the role of Islamic finance in this regard and how Islamic finance principles can help and support financial institutions to avoid another economic and financial crisis in the days to come. ‎